Expansion and structural change higher education in Germany, the United States, and Japan, 1870 - 1990 - Windolf, Paul 1946- (Westview Press, 1997)
Based on archival data for the United States, Germany, Japan, France, and Italy, this study combines both comparative and historical perspectives. It documents the political struggle of different social groups for access to universities, as well as the meritocratic selection for higher status positions